New ways of teaching and observing science class. (May 2015) - Hutner, Todd L.; Sampson, Victor
Observing the work of science teachers is different. Although general indicators such as a focus on relevant and appropriate topics, student engagement, frequent checks for understanding are important for any context, they're insufficient for identifying good science instruction. Science teachers need to use science-specific instructional practices due to the nature of the content and what we know about how people learn science. The authors identify five indicators of good science instruction: creating a need to learn, making student thinking visible, engaging in activities before delving into content, participating in the practices of science and having students negotiate their own meaning. In addition, the authors identify five student practices that principals should be able to see during observations: asking questions, planning, and carrying out investigations; analyzing and interpreting data; engaging in argument from evidence and obtaining, evaluating, and communicating information.